Protracted HBsAg-aemia in a Patient with Acute Hepatitis B - K. R. Dudina; O. O. Znoyko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. This clinical observation was aimed at analysing the course of the disease in a patient with a protracted persistence of HBsAg and HBV DNA in the blood in the outcome of acute hepatitis B and the possible formation of a latent HBV infection in the phase of clinical recovery.General findings. We carried out a 31-month observation study of a patient suffering from acute hepatitis B. Subsequently, we performed a dynamic assessment of the viral kinetics and qualitative and quantitative assessment of HBsAg in the blood using highly sensitive analytical methods. These methods allowed a protracted persistence of HBV DNA in the blood and a late seroconversion of HBsAg/anti-HBs to be revealed.Conclusion. The described clinical case demonstrates the possibility of an atypically protracted persistence of  HBsAg in the outcome of acute hepatitis B, which is followed by a clinical and laboratory picture of recovery and the formation of latent chronic HBV infection, as an example of the 5th phase of chronic HBV infection (HBsAg-negative), according to a new classification, reflected in the clinical guidelines for the treatment of hepatitis B (EASL 2017).